Four novel ARSA gene mutations with pathogenic impacts on metachromatic leukodystrophy: a bioinformatics approach to predict pathogenic mutations - Manshadi, M.D.; Kamalidehghan, B.; Aryani, O.; Khalili, E.; Dadgar, S.; Tondar, M.; Ahmadipour, F.; Meng, G.Y.; Houshmand, M. (Dove Medical Press, 2017)
Metachromatic leukodystrophy (MLD) disorder is a rare lysosomal storage disorder that leads to severe neurological symptoms and an early death. MLD occurs due to the deficiency of enzyme arylsulfatase A (ARSA) in leukocytes, and patients with MLD excrete sulfatide in their urine. In this study, the ARSA gene in 12 non-consanguineous MLD patients and 40 healthy individuals was examined using polymerase chain reaction sequencing. Furthermore, the structural and functional effects of new mutations on ARSA were analyzed using SIFT (sorting intolerant from tolerant), I-Mutant 2, and PolyPhen bioinformatics software. Here, 4 new pathogenic homozygous mutations c.585G>T, c.661T>A, c.849C>G, and c.911A>G were detected. The consequence of this study has extended the genotypic spectrum of MLD patients, paving way to a more effective method for carrier detection and genetic counseling.